SCDT-17. DECREASED OPERATIVE COMPLICATIONS WITH IMAGE-GUIDED OMMAYA RESERVOIR INSERTION: SYSTEMATIC REVIEW AND META-ANALYSIS. (6th November 2017) - Lau, Jonathan; Kosteniuk, Suzanne; Walker, Tom; Iansavichene, Alla; Macdonald, David; Megyesi, Joseph
Abstract: OBJECTIVE: One of the classic technologies facilitating therapeutic drug delivery to the central nervous system (CNS) is the Ommaya reservoir. Subcutaneous Ommaya reservoir insertion (ORI) has been available as a treatment option for targeted intraventricular pharmacotherapy since the 1960's. The intraventricular catheter has conventionally been inserted freehand. However, advancements in image-guidance (IG) over the past two decades has enabled IG-ORI as a viable, and arguably preferred, alternative to blind insertion. In this study, we sought to compile evidence from the literature about surgical outcome in ORI to assess the impact of IG on safety and efficacy. METHODS: A systematic review and meta-analysis of operative outcomes from ORI was performed using Medline and Embase databases in compliance with standard guidelines. Patient demographics, surgical details, and peri-operative outcomes (hemorrhage, infection, malposition, malfunction, overall morbidity and mortality) were extracted from the full-text of included articles. Study quality was assessed via MINORS criteria. Random effects and heterogeneity analysis were performed. RESULTS: 45 studies met study criteria, for a total of 2075 independent ORIs. Pooled rates of outcome for IG compared to non-IG were 6.0% versus 13.0% for overall complications; 2.1% compared to 2.9% for catheter malfunction; 1.7% compared to 3.0% for catheter malposition; 0.8% compared to 4.2% for early post-operative infection; 0.4% compared to 1.4% for mortality. Interestingly, post-operative hemorrhage was increased at 3.8% compared to 2.3%. There was an overall trend towards decreased complications with date of publication (Pearson correlation = -0.606). The reported analyses all met the threshold for statistical significance (p-value < 0.05). CONCLUSION: IG was associated with decreased overall complication, catheter malfunction/malposition, and early post-operative infection rates. Increased hemorrhage rates are likely the result of increased routine post-operative imaging concurrent with the IG era. Although the overall quality of evidence is low, this meta-analysis provides objective support for IG-ORI.